2011
DOI: 10.14742/ajet.922
|View full text |Cite
|
Sign up to set email alerts
|

Are secondary preservice teachers well prepared to teach with technology? A case study from China

Abstract: <span>This case study investigates how well secondary preservice teachers are prepared to use technology in teaching in China. The study focuses on a teacher education program that is a representative of many of those in mid-sized Chinese universities. It examines participants' experiences with, perspectives of, and expectations about the use of technology and the training they are receiving in this area. Data collected through survey and interviews indicate that research participants have similar perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Further, the results are in agreement with the study of Mereku et al (2008) in Ghana that HEIs provide little opportunity for students to learn skills necessary to integrate technology in learning. Likewise, in China and Nigeria, Zhou et al (2011) and Garba and Alademerin (2014) found that students were not well prepared to use technology tools in their learning respectively. Brooks and Grajek (2020) also found that majority of students had not received any e-learning training.…”
Section: What Is the Perception And Readiness Of Students For Online mentioning
confidence: 99%
“…Further, the results are in agreement with the study of Mereku et al (2008) in Ghana that HEIs provide little opportunity for students to learn skills necessary to integrate technology in learning. Likewise, in China and Nigeria, Zhou et al (2011) and Garba and Alademerin (2014) found that students were not well prepared to use technology tools in their learning respectively. Brooks and Grajek (2020) also found that majority of students had not received any e-learning training.…”
Section: What Is the Perception And Readiness Of Students For Online mentioning
confidence: 99%
“…Research has indicated that pre-service teachers have concerns about technology integration (Cullen & Greene, 2011;Hur et al, 2015;Zhou, Zhang, & Li, 2011). The results of this study identified four major concerns of pre-service teachers involved in this study: resources, technology skills, subject area and students.…”
Section: Implications For Practicementioning
confidence: 77%
“…Research has identified that pre-service teachers have concerns about technology integration (e.g., their future school would lack technology resources; technology is not applicable in their subject areas; they are concerned about their own technology skills) (Cullen & Greene, 2011;Hur, Shen, Kale, & Cullen, 2015;Zhou, Zhang, & Li, 2011). Modelling and mentoring have been highlighted as a means of overcoming these concerns (Tharp & Dirksen, 1996;Kim & Baylor, 2008).…”
Section: Modelling and Mentoringmentioning
confidence: 99%
“…ITE has focused on preparing the stereotype of the 'digital native' to participate, shape, and lead digital pedagogy (Donnison, 2009;Zhou, Zhang, & Li, 2011). However, the literature now shows the majority of STs do not fit or identify with this definition (Corrin, Bennett, & Lockyer, 2010, White & Le Cornu, 2011.…”
Section: Literature Reviewmentioning
confidence: 99%